2017
DOI: 10.1111/nicc.12325
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of subjective sedation scales used for critically ill paediatric patients

Abstract: Aims: This study evaluated the psychometric properties of subjective sedation scales using one psychometric scoring system to identify the appropriate scale that is most suitable for clinical care practice. Background: A number of published sedation assessment scales for paediatric patients are currently used to attempt to achieve a moderate depth of sedation to avoid the undesirable effects caused by over-or undersedation. However, there has been no systematic review of these scales. Search strategy: We searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…). As the intubated children cannot express themselves, especially when in a critical condition or when administered a neuromuscular blockade agent, the nurses must resort to observing the physiological and behavioural responses (Chanques et al ., ; Dijk et al ., ), which have been supported by several systematic reviews (Dorfman et al ., ; Ge et al ., ; Grap et al ., ) focusing on the instruments for scoring sedation cues to pain and distress. In 2016, the ESPNIC published a position statement regarding the clinical recommendations for sedation, which suggested some validated tool for intubated children in PICUs.…”
Section: Discussionmentioning
confidence: 97%
“…). As the intubated children cannot express themselves, especially when in a critical condition or when administered a neuromuscular blockade agent, the nurses must resort to observing the physiological and behavioural responses (Chanques et al ., ; Dijk et al ., ), which have been supported by several systematic reviews (Dorfman et al ., ; Ge et al ., ; Grap et al ., ) focusing on the instruments for scoring sedation cues to pain and distress. In 2016, the ESPNIC published a position statement regarding the clinical recommendations for sedation, which suggested some validated tool for intubated children in PICUs.…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review showed many gaps in the original validation of the RS and that its psychometric properties were poor for children. 9 Despite including patients ≥8 years, the original RS article does not include information on interrater and intrarater reliability, construct validity, criterion validity, or applicability for children. This, coupled with the fact that there are no subsequent validation studies in pediatrics, make their psychometric properties poor in this population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed many gaps in the original validation of the scale and that its psychometric properties were poor for children. 9 The scale uses auditory and tactile stimuli to measure sedation at deep levels, which interferes with the procedure (mainly procedures with immobility) and increases the probability of subjectivity. It cannot be used on relaxed patients or on those that are agitated, given that agitation is only described in level one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several sedation scales have been developed to assist clinicians in achieving this delicate balance, but which instrument to choose may not always be so clear. This led Ge et al (2018) to conduct a systematic review of all articles evaluating the psychometric properties of sedation scales among children and adolescents. Forty-three papers examining 13 sedation scales were retrieved and appraised using Robinson et al's (2013) scoring system, which was re-evaluated by a team of experts through a structured Dephi method.…”
Section: What's In This Issuementioning
confidence: 99%